PENINGKATAN KETERAMPILAN MEMBACA PUISI MELALUI MEDIA AUDIO VISUAL SISWA KELAS V SDN ROWOSARI 02 SEMARANG - Djariyo Djariyo; Ainun Alifah (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2013)
This research is motivated by the skills of reading poetry is very low, students can not read poetry properly, the students have not dared to read poetry in front of the class with its own style and expression. issues that will be studied in the research of this class action is whether the audio-visual media can improve the skills of reading poetry Grade V SDN Rowosari 02 academic year 2011/2012.The hypothesis of this study is if the action using optimal audio-visual media in the learning process of poetry, the poetry reading skills of students of class V SDN Rowosari 02 of 2011/2012 will increase.Results of the first cycle of learning research shows that activity pramembaca process, while reading, and there are shortcomings pascamembaca among others seen in the stage pramembaca students have not been able to analyze the situation and audience, selecting text, dissect manuscripts and training; current stage readings students have not been able to appreciate the content of poetry, and performances; pascamembaca stage students have not been able to evaluate what is right and wrong. Results of the first cycle, the average value reached 6.31. In the second cycle there is an increase in the lan: pramembaca stage students can analyze the situation and audience, selecting text, dissect manuscripts and training; the current stage of reading students can appreciate and look quite good; pascamembaca stage students can evaluate the poems were read. Results of the second cycle, the average value increased to 6.92. Cycle III there is a significant increase, especially on the vocal aspect and appearance, while aspects of the interpretation of the students can appreciate good, although not perfect. Results of the third cycle of the average value increased to 7.49.Based on the three cycles of the above, the conclusion that there is an increase in the learning acquired reading poetry through audio-visual media. In the first cycle there is an increase of 6.34%, increased by 14.59% second cycle and third cycle increased by 21.10%. In this study, the researchers propose suggestions to teachers and readers of poetry to improve reading skills through audio-visual media by providing examples of good poetry readings and true.